The prognostic value of abnormally expressed lncRNAs in prostatic carcinoma: A systematic review and meta-analysis. Issue 51 (December 2017) - Wu, Xian-Lan; Zhang, Ji-Wang; Li, Bai-Song; Peng, Shu-Sheng; Yuan, Yong-Qiang
Abstract: Background: Several long noncoding RNAs (lncRNAs) are abnormally expressed in prostate cancer (PCa), suggesting that they could serve as novel prognostic markers. The current meta-analysis was undertaken to better define the prognostic value of various lncRNAs in PCa. Methods: The PubMed, Embase, Medline, and Cochrane Library databases were systematically searched up to February 19, 2017, to retrieve eligible articles. Outcomes analyzed were biochemical recurrence-free survival (BRFS), overall survival (OS), metastasis-free survival (MFS), and prostate cancer-specific survival (PCSS). Pooled hazard ratios (HRs) and 95% confidence intervals (95%CIs) were calculated using fixed-effects or random-effects models. Results: A total of 10 studies, evaluating 11 PCa-related lncRNAs, were included in the meta-analysis. Pooled results indicate that the abnormal expression of candidate lncRNAs in PCa samples predicted poor BRFS (HR: 1.67, 95%CI: 1.37–2.04, P < .05), without significant heterogeneity among studies ( I 2 = 44%, P = .06). Low PCAT14 expression was negatively associated with OS (HR: 0.66, 95%CI: 0.54–0.79, P < .05), MFS (HR: 0.59, 95%CI: 0.48–0.72, P < .05), and PCSS (HR: 0.50, 95%CI: 0.38–0.66, P < .05). Again, there was no significant heterogeneity among studies. The robustness of our results was confirmed by sensitivity and publication bias analyses. Conclusion: We conclude that expression analysis of selected lncRNAs may be of prognostic value in PCa patients.